Community-based referral for tuberculosis preventive therapy is effective for treatment completion - Sheela V. Shenoi; Tassos C. Kyriakides; Emily Kainne Dokubo; Vijayanand Guddera; Peter Vranken; Mitesh Desai; Gerald Friedland; Anthony P. Moll (Public Library of Science (PLoS), 2022)
Expansion of tuberculous preventive therapy (TPT) is essential to curb TB incidence and mortality among people with HIV (PWH), yet implementation has been slow. Innovative strategies to operationalize TPT are urgently needed. Here we present an evaluation of community-based identification and referral of PWH on completion of a six-month course of isoniazid in a highly prevalent region in rural South Africa. Using a community-based TB/HIV intensive case finding strategy, a team of nurses and lay workers identified community members with HIV who were without fever, night sweats, weight loss, or cough and referred them to the government primary care clinics for daily oral isoniazid, the only available TPT regimen. We measured monthly adherence and six-month treatment completion in the community-based identification and referral (CBR) group compared to those already engaged in HIV care. Adherence was measured by self-report and urine isoniazid metabolite testing. A multivariable analysis was performed to identify independent predictors of TPT completion. Among 240 participants, 81.7% were female, median age 35 years (IQR 30-44), and 24.6% had previously been treated for TB. The median CD4 count in the CBR group was 457 (IQR 301-648), significantly higher than the clinic-based comparison group median CD4 of 344 (IQR 186-495, p<0.001). Independent predictors of treatment completion included being a woman (aOR 2.41, 95% 1.02-5.72) and community-based identification and referral for TPT (aOR 2.495, 95% 1.13-5.53). Among the CBR group, treatment completion was 90.0%, an absolute 10.8% higher than the clinic-based comparison group (79.2%, p = 0.02). Adherence was significantly greater in the CBR group than the clinic-based comparison group, as measured by self-report (p = 0.02) and urine isoniazid testing (p = 0.01). Among those not on ART at baseline, 10% of eligible PWH subsequently initiated ART. Community members living with HIV in TB endemic regions identified and referred for TPT demonstrated higher treatment completion and adherence compared to PWH engaged for TPT while receiving clinic-based care. Community-based identification and referral is an innovative adjunctive strategy to facilitate implementation of TB preventive therapy in people living with HIV.